TSG Extends the Longevity of Caenorhabditis elegans by Targeting the DAF-16/SKN-1/SIR-2.1-Mediated Mitochondrial Quality Control Process - Menglu Sun; Congmin Wei; Yehui Gao; Xinyan Chen; Kaixin Zhong; Yingzi Li; Zhou Yang; Yihuai Gao; Hongbing Wang (MDPI AG, 2024)
The improvement of mitochondrial function is described as a strategy for alleviating oxidative stress and intervening in the aging process. 2,3,5,4'-Tetrahydroxystilbene-2-O-β-D-glucoside (TSG) is one of the major bioactive components isolated from Polygonum multiflorum Thunb, and it exhibits multiple activities, including antioxidant and anti-inflammatory effects. In this study, we found that 200 μM TSG significantly extended the mean lifespan of Caenorhabditis elegans by 16.48% and improved health status by delaying age-associated physiological decline in worms. The longevity prolongation effect of TSG depended on the regulation of the mitochondrial quality control process mediated by DAF-16/FOXO, SKN-1/Nrf2 and SIR-2.1/SIRT1 to improve mitochondrial function. Moreover, TSG treatment obviously alleviated the proteotoxicity of β-amyloid and tau proteins in worms. Our findings indicated that TSG is a promising natural product for preventing aging and treating aging-associated neurodegenerative diseases by regulating the mitochondrial quality control process to improve mitochondrial function.